Plasma Fibrinogen-Like Protein 2 Levels in Patients with Non-Alcoholic Fatty Liver Disease - YILMAZ, YUSUF (H G E UPDATE MEDICAL PUBLISHING S A, 2011)
Background/Aims: Fibrinogen-like protein 2 (fgl2), has recently been identified as a new member of the fibrinogen-like family of proteins. In this study we assayed plasma levels of fgl2 in patients with biopsy proven non-alcoholic fatty liver disease (NAFLD) and examined their association with clinical, biochemical and histological phenotypes. Methodology: Levels of plasma fgl2 were measured by enzyme linked immunosorbent assay and compared between the study groups. Moreover, concentrations of fgl2 were assessed in relation to the general characteristics of the study participants and the results of the liver biopsy. Results: Levels of fgl2 were significantly higher in patients with definite non-alcoholic steatohepatitis (NASH) (788 +/- 190pg/mL, p<0.001) and borderline NASH (710 +/- 140pg/mL, p<0.001) compared with controls (515 +/- 174pg/mL). No significant differences were found in patients with simple steatosis (649 +/- 162pg/mL) as compared with controls. There were no associations between the plasma fgl2 levels with the fibrosis stage and steatosis grade. Conclusions: Although subject to future confirmation, our data suggest that fgl2 levels are elevated in the more severe forms of NAFLD.
Keywords: Non-alcoholic fatty liver disease; Non-alcoholic steatohepatitis; Fibrinogen-like protein 2; STEATOHEPATITIS; CONTRIBUTES; NAFLD; FGL2